PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM MEMAHAMI KISAH KETELADANAN WALI SONGO - Tuti Suprapti (Universitas Pakuan, 2019)
THE AUDIO-VISUAL MEDIA IN IMPROVE STUDENT LEARNING OUTCOMES TO UNDERSTAND STORY OF WALISONGO RELIGION This research is a Classroom Action Research (CAR) conducted at primary school (SD Negeri Kampung Sawah) in Bogor Utara District at Semester 2 of the 2017-2018 Academic Year. The research was conducted in two cycles, each cycle consisting of four stages, namely: planning, implementation, observation and reflection. The minimal completeness criteria is when a minimum score of 75(quite active). Benchmarks for success in this class action research are if the learning outcomes of PAI learners grade IV B SDN Kampung Sawah District Bogor Utara Bogor City in the last cycle if the KKM 75 Students who reach the KKM are above 75%, Students are active in learning above 75% Activity teachers during the learning process above 75% The analysis found that there was an increase in the activity and competence of teachers in preparing the Student Worksheet from cycle I to cycle II. Achievement of performance indicators is in action II. Thus, it can be said that cluster activities can improve the competence of students in Kampung Sawah State Primary School, North Bogor District, Bogor City Semester 2 2017-2018 Academic Year. The teacher gave a positive response to the results of the workshop in the Cluster. The results showed that audio-visual media can improve student learning outcomes, especially about understanding the exemplary story of Wali Songo in Kampung Sawah State Elementary School. Thus it can be recommended to providers, friends or other researchers to use audio-visual media to improve student learning outcomes that are carried out continuously. The use of audio-visual media can improve student learning outcomes, especially in public elementary schools in improving student achievement